2013
DOI: 10.1158/1078-0432.ccr-11-2524
|View full text |Cite
|
Sign up to set email alerts
|

PRAME-Induced Inhibition of Retinoic Acid Receptor Signaling-Mediated Differentiation—A Possible Target for ATRA Response in AML without t(15;17)

Abstract: Purpose: In acute myeloid leukemia (AML) without retinoic acid receptor (RAR) rearrangement, the effect of all-trans-retinoic acid (ATRA) is still poorly understood despite an association of NPM1 mutation and ATRA response. Recently, preferentially expressed antigen in melanoma (PRAME) has been shown to be a dominant repressor of RAR signaling.Experimental Design: Thus, we further investigated ATRA response mechanisms, especially the impact of PRAME expression on ATRA responsiveness. We profiled gene expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
0
24
0
3
Order By: Relevance
“…MN1, another commonly overexpressed oncogene in AML, directly binds to RAR to inhibit retinoic acid signaling 35 . Bullinger et al have recently reported overexpression of PRAME1, a member of the RAR-associated co-repressor complex, in AML 36 : interestingly, high levels of PRAME were associated with ATRA responsiveness in the ULM AML 07-04 trial.…”
Section: Is Rar Functional In Aml?mentioning
confidence: 98%
“…MN1, another commonly overexpressed oncogene in AML, directly binds to RAR to inhibit retinoic acid signaling 35 . Bullinger et al have recently reported overexpression of PRAME1, a member of the RAR-associated co-repressor complex, in AML 36 : interestingly, high levels of PRAME were associated with ATRA responsiveness in the ULM AML 07-04 trial.…”
Section: Is Rar Functional In Aml?mentioning
confidence: 98%
“…Only minimal positive shifts in median fluorescence intensity (MFI) After the preliminary biochemical and specificity characterization, we sought to determine whether Pr20 could recognize cancer cells expressing endogenous PRAME protein. PRAME mRNA expression was assessed by quantitative PCR (qPCR), and surface HLA-A2 expression and Pr20 binding were assessed by flow cytometry across a panel of HLA-A2 + hematopoietic and solid tumor cell lines, several of which have been reported to express PRAME by other groups (10,12,16,30,31) (Table 1 and Figure 1C). Pr20 binding was readily detected in PRAME + HLA-A2 + leukemia AML14, SET2, BV173, and the T cell lymphoma MAC2A, demonstrating that Pr20 can detectably bind endogenously processed and presented peptides ( Figure 1D).…”
Section: Pr20 Binds To Aly/hla-a2 Complexes In Prame/hla-a2-expressinmentioning
confidence: 99%
“…Вероятно, это вызвано большей доступностью лейкозных клеток, циркулирующих в крови, для иммунной атаки. Однако при ОМЛ не наблюдается PRAME-опосредованного снижения уровня экспрессии гена TRAIL [71]. При этом результаты экспериментов с клеточными линиями не упрощают объяснение позитивного значения экспрессии PRAME при ОМЛ.…”
Section: парадоксальность Prameunclassified
“…При этом результаты экспериментов с клеточными линиями не упрощают объяснение позитивного значения экспрессии PRAME при ОМЛ. Так, клетки линии KG1 после трансфекции (процесс введения нуклеиновой кислоты в клетки эукариот невирусным методом) геном PRAME медленнее росли, хуже формировали колонии, а интенсивность каспаза-3-независимого апоптоза в них увеличивалась [67,69,71]. В то же время клетки линий HL60 и NB4 после трансфекции геном PRAME повышали скорость пролиферации [9].…”
Section: парадоксальность Prameunclassified
See 1 more Smart Citation